2019
DOI: 10.3389/fgene.2018.00737
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Selection Signatures Among Brazilian, Sri Lankan, and Egyptian Chicken Populations Under Different Environmental Conditions

Abstract: Extreme environmental conditions are a major challenge in livestock production. Changes in climate, particularly those that contribute to weather extremes like drought or excessive humidity, may result in reduced performance and reproduction and could compromise the animal’s immune function. Animal survival within extreme environmental conditions could be in response to natural selection and to artificial selection for production traits that over time together may leave selection signatures in the genome. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 59 publications
1
36
0
Order By: Relevance
“…The most representative gene on chromosome 7, with regards to production traits, is FTCD, which plays a main role in feed intake, in accordance with the quantitative trait loci identified [40]. Inside the last region identified on chromosome 8, the TRMT1L (tRNA Methyltransferase 1-Like) gene is noteworthy as it seems to be involved in chicken adaptation and survival in stressful conditions [41].…”
Section: Discussionsupporting
confidence: 62%
“…The most representative gene on chromosome 7, with regards to production traits, is FTCD, which plays a main role in feed intake, in accordance with the quantitative trait loci identified [40]. Inside the last region identified on chromosome 8, the TRMT1L (tRNA Methyltransferase 1-Like) gene is noteworthy as it seems to be involved in chicken adaptation and survival in stressful conditions [41].…”
Section: Discussionsupporting
confidence: 62%
“…The hapFLK statistic that accounted for the haplotype information and hierarchical structure [36, 37] was used to identify selection footprints on the contrast model (river vs. swamp). HapFLK analyses revealed that a total of 12 genomic regions was identifed ( Fig 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…In Africa, local chickens are raised in free range scavenging and backyard systems ( Goromela et al, 2006 ). As a result, African local chicken ecotypes are adapted to extreme climatic conditions with low inputs of feed and veterinary services, as evidenced by the presence of selection signatures across the genomes of local chickens ( Fleming et al, 2016 , 2017 ; Walugembe et al, 2019a ). Although local chickens are well adapted to their environment and some unvaccinated local chickens have been reported to have anti-NDV antibodies ( Boakye et al, 2016 ), velogenic ND outbreaks often lead to loss of entire chicken flocks ( Guèye, 2002 ; Copland et al, 2018 ) due to lack of or ineffective vaccination.…”
Section: Introductionmentioning
confidence: 99%